THE IMPLEMENTATION OF MARKETING MIX STRATEGY AT EVENTA ORGANIZER - Pebriana, Nur Rahmi Anugrah; Wahid, Abdul; Asfah, Indrawaty (Universitas Negeri Makassar, 2023)
The event product marketing strategy is one of the marketing strategies implemented through organizing events that aim to promote brands, products, or services. By knowing the marketing strategy, it is hoped that the marketing activities carried out can achieve goals effectively and efficiently. Companies must know the stages of implementing marketing strategies, starting from external and internal factors, to identify factors that become opportunities, threats, strengths, and weaknesses. The purpose of this study is to examine how Eventa Organizer implemented the 4P marketing mix strategy. This study used the descriptive qualitative method. Data collection was carried out using observation, documentation, and interviews. In this study, the objects of research were two, namely the director and employees of the marketing division of the event organizer. The results of this study show that the 4P marketing mix strategy used by Eventa Organizer is good. In the implementation of the marketing mix strategy, Eventa Organizer has had stable sales since the company was initiated so the products produced by Eventa Organizer make successful events, where the objectives of the event are achieved and the participants or guests are satisfied with the experience they get.